2007
DOI: 10.1021/ef070149x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Diesel Fuel Effects on Direct Injection (DI) Diesel Engine Performance and Pollutant Emissions

Abstract: An experimental investigation was conducted to specify the effect of diesel fuel composition and its physical and chemical properties on direct injection (DI) diesel engine performance characteristics and pollutant emissions. Engine tests were made on a single-cylinder naturally aspirated DI diesel engine (Lister LV1), which is located at the laboratory of the authors, at various operating conditions using seven conventional diesel fuels. The test fuels indicate variable hydrocarbon composition and physical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…The higher CN, the better in fuel burns within the engine of a vehicle. The difference between CN and octane number (ON) is that ON rates gasoline whereas cetane rates diesel [14]. Moreover, just as higher performance gasoline vehicles require fuels with a higher ON, high performance diesel vehicles require fuel with a higher CN.…”
Section: Influence Gamma Irradiation On Cetane Number Of Diesel Fuelmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher CN, the better in fuel burns within the engine of a vehicle. The difference between CN and octane number (ON) is that ON rates gasoline whereas cetane rates diesel [14]. Moreover, just as higher performance gasoline vehicles require fuels with a higher ON, high performance diesel vehicles require fuel with a higher CN.…”
Section: Influence Gamma Irradiation On Cetane Number Of Diesel Fuelmentioning
confidence: 99%
“…The most important properties of diesel fuels are [14] viscosity, heating value, ignition quality, volatility, cetane number, lubricity, low-temperature flow, component compatibility, storage stability, and sulfur content [15]. Andrade et al 2014 [16] have described the hydrodesulphurization (HDS), which is currently the most common method used by refineries to remove sulfur compounds from petroleum fractions.…”
Section: Introductionmentioning
confidence: 99%
“…Zannis et al [12] conducted experiments in conventional diesel engines, and they reported that reductions of soot, NO and CO emissions could be achieved with the reduction of distillation temperature and an increase of paraffin/naphthene ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Diesel engines are preferred by ICE manufacturers because of their high output power and thermal performance [7]. The current effects produced by global warming and air pollution together with the variations in the prices of fossil fuels, require alternative solutions to promote the reduction of specific fuel consumption and emissions of polluting gases from stationary diesel engines and diesel vehicles [8].…”
Section: Introductionmentioning
confidence: 99%